Pembangunan Sistem Pemesanan Lapangan Futsal berbasis Web (Studi Kasus: Zona SM Futsal Malang) - Miftahul Arifin; Agus Wahyu Widodo; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The management of the futsal field affects the success of this business. In handling business activities, it often experiences obstacles in the order process, transaction management, transaction recapitulation, and transaction reports. This problem occurs in the futsal field at Zona SM Malang , in the organization of transactions still using the offline system by recording orders, making proofs with paper, making a data recap that the manager has difficulty because there is a lot of paper to be collected and also unorganized storage of ordering data for field use. Futsal properly and correctly so that the data will be lost. For the ordering system, tenants must come to Zona Malang SM location to place an order. As a futsal court, ZONA SM requires an order system to manage transaction data and ordering systems. Based on these problems, it is to improve the effectiveness of the field ordering process and data management in Zona SM Malang Futsal. The system development in this study uses the SDLC waterfall with an object oriented approach, the design stage uses UML modeling which can be used to make implementations, the system is built using the programming language PHP, HTML, and CSS. For databases using MySQL. The testing phase on functional requirements uses blackbox testing and whitebox testing and shows 100% valid results on both tests. Testing for non-functional requirements uses browser compatibility testing and shows the results that the system is compatible in various browsers.